Romeo & Juliet - Shakespeare, William (Sl : 20th Century Fox, 2002)
Summary: The Brilliant and Contemporary re-telling of the most tragic love affair of Romeo and Juliet.
Keywords: Shakespear, William, 1564-1616 -- Adaptations; Film adaptations; International Baccalaureate; Film